Human pluripotent stem cell‐derived epicardial progenitors can differentiate to endocardial‐like endothelial cells. Issue 2 (22nd May 2017) - Bao, Xiaoping; Bhute, Vijesh J.; Han, Tianxiao; Qian, Tongcheng; Lian, Xiaojun; Palecek, Sean P.
Abstract: During heart development, epicardial progenitors contribute various cardiac lineages including smooth muscle cells, cardiac fibroblasts, and endothelial cells. However, their specific contribution to the human endothelium has not yet been resolved, at least in part due to the inability to expand and maintain human primary or pluripotent stem cell (hPSC)‐derived epicardial cells. Here we first generated CDH5‐2A‐eGFP knock‐in hPSC lines and differentiated them into self‐renewing WT1+ epicardial cells, which gave rise to endothelial cells upon VEGF treatment in vitro . In addition, we found that the percentage of endothelial cells correlated with WT1 expression in a WT1‐2A‐eGFP reporter line. The resulting endothelial cells displayed many endocardium‐like endothelial cell properties, including high expression levels of endocardial‐specific markers, nutrient transporters and well‐organized tight junctions. These findings suggest that human epicardial progenitors may have the capacity to form endocardial endothelium during development and have implications for heart regeneration and cardiac tissue engineering.